Сonnection between appearance itself and by the level of sense of life - A. Marcinyak-Dorosh, (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
This article examines connection between self-perception and the level of feeling of sense of life in overweight and obese women and in pa- tients suffering from saccharine diabetes. This research shows that these women have a negative perception of self which, in turn, influences nega- tively their level of feeling of sense of life. The research results may prove useful in developing a plan for overweight and obesity treatment.
Keywords: perception of Self; feeling of sense of life; obesity; saccharine diabetes; Real Self; Ideal Self